ANALISIS EFISIENSI PENGGUNAAN MODAL DAN TENAGA KERJA PADA INDUSTRI SANGGAH DI KECAMATAN TEMBUKU KABUPATEN BANGLI - Dewi, Putu Agustini Sukma; Wenagama, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 10 No 2 (2021): VOL 10 NO 2, FEBRUARI 2021 [ 451 - 898], 2021)
The growth of the industrial sector is strongly influenced by the level of production, if the larger the production, it will show the level of efficiency in the use of production factors or high inputs. The purpose of this study simultaneously and partially is to determine the effect of capital and labor on production and to determine the level of efficiency. The data used in this study are primary data, namely by distributing questionnaires to the owners of the handicraft business in Tembuku District. The sample used in this study were 52 business units in Tembuku District. The sample technique used is non probability sampling. Using multiple linear regression analysis techniques. The results showed that capital and labor simultaneously had a significant effect on production. Capital partially has a significant effect on production, labor partially has a significant effect on production. The level of efficiency of capital and labor is efficient. The variable that most influences production is capital. Keywords: Capital, Labor, Production